2017
DOI: 10.21037/sci.2017.08.01
|View full text |Cite|
|
Sign up to set email alerts
|

Into the eyes of bone marrow-derived mesenchymal stem cells therapy for myocardial infarction and other diseases

Abstract: Applications of bone marrow-derived mesenchymal stem cells (BM-MSCs) have been documented for diseases occur in the sports system, the central nervous system, the cardiovascular system etc. However, poor viability of donor stem cells after transplantation limits their therapeutic efficiency. Although the autophagy theory has been reported, the underlying mechanisms are still poorly understood. Isolation and culture methods of mesenchymal stem cells are currently concentrate on four ways. Overall, BM-MSCs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Although platelet-rich fibrin tends to have a more replicable process than platelet-rich plasma, platelet-rich fibrin provides a higher white blood cell concentration than platelet-rich plasma, then we opted to use leukocyte-poor PRP to obtain lower leukocyte concentration to decrease the chance of inducing excessive inflammation after intra-articular administration [ 26 , 27 , 28 ]. Bone marrow is another biological product that has been used to treat musculoskeletal, cardiovascular, urinary, respiratory, digestive, integumentary and central nervous pathologies because of the potential to repair injured tissue [ 29 , 30 , 31 ] and has shown promising outcomes for various orthopedic conditions, including osteochondral defect and osteoarthritis [ 21 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although platelet-rich fibrin tends to have a more replicable process than platelet-rich plasma, platelet-rich fibrin provides a higher white blood cell concentration than platelet-rich plasma, then we opted to use leukocyte-poor PRP to obtain lower leukocyte concentration to decrease the chance of inducing excessive inflammation after intra-articular administration [ 26 , 27 , 28 ]. Bone marrow is another biological product that has been used to treat musculoskeletal, cardiovascular, urinary, respiratory, digestive, integumentary and central nervous pathologies because of the potential to repair injured tissue [ 29 , 30 , 31 ] and has shown promising outcomes for various orthopedic conditions, including osteochondral defect and osteoarthritis [ 21 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…studied and hold great promise for treating a variety of immunemediated diseases and/or tissue defects. 34 The patch-clamp analysis demonstrated that functional L-VGCCs are expressed in about 15% of human undifferentiated BMSCs, 35,36 which was similar to rat BMSCs, 37 whereby calcium entry through L-VGCCs has a significant impact on BMSCs properties. One study investigated the role of L-VGCCs in the proliferation of rat BMSCs and found that blockade of L-VGCCs by nifedipine had suppressed their proliferation.…”
Section: L-vgccs and Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 94%
“…Bone marrow‐derived mesenchymal stem cells (BMSCs) are acquired mainly from bone marrow, where they account for <0.0001% of all cells. Considering the advantages of easy accessibility, multipotent differentiation and low immunogenicity, BMSCs have been widely studied and hold great promise for treating a variety of immune‐mediated diseases and/or tissue defects . The patch‐clamp analysis demonstrated that functional L‐VGCCs are expressed in about 15% of human undifferentiated BMSCs, which was similar to rat BMSCs, whereby calcium entry through L‐VGCCs has a significant impact on BMSCs properties.…”
Section: L‐vgccs and Mscsmentioning
confidence: 96%
“…In addition, MSCs exhibit low expression of major histocompatibility complex (MHC)-I molecules and are negative for MHC-I [11], which is beneficial for the success of autologous and allogeneic transplantation. In view of their aforementioned advantages, MSCs are considered an ideal candidate for repairing or regenerating desired tissue at present [12,13]. However, a series of researches revealed the self-renewal ability and multipotency of MSCs would decline and even lose along the consecutive passage in vitro , during which cellular senescence has been suggested to occur [14–18].…”
Section: Introductionmentioning
confidence: 99%